2016 Research on Equity and Sustained Participation in Engineering, Computing, and Technology (RESPECT) 2016
DOI: 10.1109/respect.2016.7836165
|View full text |Cite
|
Sign up to set email alerts
|

Does a taste of computing increase Computer Science enrollment?

Abstract: Abstract-This study investigated the impact of the ExploringComputer Science (ECS) program on the likelihood that students of all races and gender would pursue further computer science coursework in high school. ECS is designed to foster deep engagement through equitable inquiry around computer science concepts. If the course provides a meaningful and relevant experience, it will increase students' expectancies of success as well as increase their perceived value for the field of computer science. Using survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The results indicate that students subject to the graduation requirement took additional CS coursework at a much lower rate (13%) than students who took ECS as an elective (43%) [4]. However, the total number of students taking ECS has significantly increased, so the total number of students taking additional CS will also continue to increase.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results indicate that students subject to the graduation requirement took additional CS coursework at a much lower rate (13%) than students who took ECS as an elective (43%) [4]. However, the total number of students taking ECS has significantly increased, so the total number of students taking additional CS will also continue to increase.…”
Section: Discussionmentioning
confidence: 97%
“…It quickly grew to include around 4600 students in the year before the graduation requirement. Almost half of the students who took ECS as an elective class (43%) went on to take additional high school computer science coursework, compared to one quarter of the students (26%) who started with a different computer science class [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have successfully documented the impact of this professional development on the quality of ECS implementation [13]. Prior studies have also shown that students' perceptions of the relevance of the ECS course experiences influence students' attitudes towards computer science and influence the likelihood that students will pursue further computer science coursework [6,19].…”
Section: Introductionmentioning
confidence: 99%
“…This may form a particularly nice integration of the programming, data analysis, and robotics units of the Exploring Computer Science (ECS) curriculum [4], which has been implemented in many high schools in the United States. Initiated in Los Angeles, ECS is now in the seven largest US school districts and many other locations [3], and it has had a particularly strong impact in Chicago [1,13]; it is also attracting some international attention.…”
Section: Introductionmentioning
confidence: 99%